2020
DOI: 10.1186/s12889-020-08951-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Indian diet with the EAT-Lancet reference diet

Abstract: Background: The 2019 EAT-Lancet Commission report recommends healthy diets that can feed 10 billion people by 2050 from environmentally sustainable food systems. This study compares food consumption patterns in India, from different income groups, regions and sectors (rural/urban), with the EAT-Lancet reference diet and highlights the deviations. Methods: The analysis was done using data from the Consumption Expenditure Survey (CES) of a nationally representative sample of 0.102 million households from 7469 vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 20 publications
9
105
0
Order By: Relevance
“…5 ). This finding is consistent with previous studies by Panda et al (2015) and Sharma et al (2020) , that indicate that Indian diets are heavy on starch and lack intake of more nutritious food.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…5 ). This finding is consistent with previous studies by Panda et al (2015) and Sharma et al (2020) , that indicate that Indian diets are heavy on starch and lack intake of more nutritious food.…”
Section: Resultssupporting
confidence: 94%
“…Table 2 reveals important heterogeneity in consumers’ physical access to various food products in both the urban and rural areas, income categories, and between the states. This heterogeneity partly explains the deficit in fruits and vegetables of eastern Indian diets ( Sharma et al, 2020 ) and may be attributed to inaccessibility of nutritious foods such as fruits and vegetables by the poor ( Bhattacharya, 2013 ; Chand and Gartia, 2016 ). Availability (i.e., whether a food item is present within a physical range) is one of the key elements of the food environment where one can see the interaction of physical distance between home and place of purchase ( HLPE, 2017 ; Turner et al, 2018 ; Downs et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were significant differences ( p < 0.001) in the average caloric intakes and estimated intakes of carbohydrates and proteins between undernourished and nourished individuals from both urban slum and rural settings. Based on the 24 h dietary recalls, the estimated daily intake of calories was less than the recommended daily intake ranging from 1,700 to 2,200 kcal ( 45 ). However, the intakes for carbohydrates, protein, and fats followed the recommended daily intakes of carbohydrates (200–320 g), proteins (42–59 g), and fats (25–30 g) in all groups ( 46 ) ( Table 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The study observed that rural to urban migration positively associated with higher fruits and vegetable intake, and negatively associated with higher energy and fat intake. Another paper (Sharma et al 2020) that compare Indian diet with EAT-lancet reference diet, used the consumption expenditure survey conducted by NSSO in 2011-12 with a sample of 0.102 million households. The paper suggested that the average daily calorie consumption was below in India than recommended except for the richest 5% of the population.…”
Section: Literature Reviewmentioning
confidence: 99%